Superconducting Gravimeter Calibration by CoLocated Gravity Observations: Results from GWR C025 - Bruno Meurers (International Journal of Geophysics)
In autumn 2007 the superconducting gravimeter GWR C025 was transferred from Vienna (VI) to the new Conrad observatory (CO) 60 km SW of Vienna. It is one of few instruments which were operated at different stations. This aspect motivated a reanalysis of all calibration experiments at VI and CO, focused on drift and noise effects. Considering the drift even of absolute gravimeters in a common adjustment reduces the root mean square error of the averaged calibration factor essentially. Also spring type gravimeters have some potential to contribute to the SG calibration factor determination. The calibration factor of GWR C025 did not significantly change during the transfer from VI to CO. The final calibration factor is calculated as weighted average over in total 9 JILAg and FG5 experiments with an accuracy of better than ±0.5‰. The calibration factor is temporarily stable with maximum variation less than ±0.1‰. Based on these results the gravity time series of VI and CO have been analyzed. The respective amplitude factors for O1, K1, and M2 agree almost perfectly at both stations after correcting for ocean loading effects. The maximum deviation from the numbers provided by the nonhydrostatic-body-tide models DDW and MAT01 is 0.8‰.